After Cancún climate governance or climate conflicts - Altvater, Elma; Brunnengräber, Achim 1963-; SpringerLink (Online service). (Wiesbaden VS Verlag für Sozialwissenschaften, 2011)
The world is facing several serious challenges at the close of the fossil and nuclear energy regime: the limited resources of cheap conventional oil can only be surmounted by tapping unconventional oil reserves, e.g. deep sea oil. The explosion of the oil platform Deepwater Horizon in 2010 and the subsequent oil spill caused enormous damage, which even a year later cannot be fully estimated. Another even more important threat emanating from the fossil and nuclear energy regime has been brought to our attention by the Fukushima disaster. Last but not least, the problem of climate change caused
Contributors; Preface; With the Market Against Climate Catastrophe -- Can That Succeed? -- Introduction; The Market: Your Friend and Helper?; On the Contributions in this Volume; Climate Capitalism; 1 Capitalism and Climate Change; 2 New sites of accumulation: Emissions trading and offsets; Emissions Trading; Offsets; 3 Making sense of the carbon economy; 4 Conclusion: Towards Climate Capitalism; References; Climate Politics as Investment; 1 Introduction; New emphasis on investments; Some remarks on theory and methodology; 2 The Economics of climate change; 2.1 Reframing climate change as an economic problem2.2 And turning climate politics into an economic challenge; 3 The new climate finance discourse; 3.1 Dominant logics in the new climate finance discourse; Estimating the costs of climate protection; Priority setting along cost effectiveness; Equity as finance; Public and private money in climate finance; 3.2 From costs to investment in climate politics; The „need for private investments" narrative; The „investment opportunity" narrative; 4 Tracing the investment logic in climate politics; Public Finance Mechanisms: Translating climate policy into investment termsREDD: Complexity, concerns, and great expectations; 5 Investments in climate politics -- some alternative framings; References; Contradictions of the Commodity Carbon -- On the Material and Symbolic Production of a Market; 1 Introduction; 2 The material and symbolic production of nature; 3 Valorisation and „occidental rationalism"; 3.1 Power and private ownership; 3.2 Exchange on markets; 3.3 Nature as Robinsonade; 3.4 Qualitative indistinguishability; 4 Own times in economics, politics and nature; References; Economic Growth and Climate Change: Cap-And-Trade or Emission Tax?1 Introduction; 2 Growth and Climate Change: Empirical Facts; 3 Growth and Climate Change: Theory and Modeling; 4 The History of Regulating Economic Externalities: Pigou versus Coase; 5 Cap-and-Trade or Carbon Taxes?; 6 European Efforts and Experiences: The high Volatility of the Carbon Price; 7 Conclusions; References; Greening the Economy in the European Union; Introduction; 1 Determination on Paper; 2 Separate Energy Regimes; 3 The Control of Nature through New Technologies and New Markets; Strategic Raw Materials Policy: Agrofuels5 Overcoming the Oil Age; References; The „Tragedy of the Atmosphere" or the Doubling of the Carbon Cycle and the Circulation of Capital; Introduction; 1 The Fossil Energy Chain -- a Carbon Cycle and a Valorisation Cycle; 2 The Tragedy of the Atmosphere; 3 Should the Pollution in the Atmosphere be Reduced by Means of Regulative Power or by „Market-based" Instruments?; 4 A few Conclusions; References; A Brief History of Emission Trading Systems; Introduction; Emissions Trading Systems.
Includes bibliographical references
Electronic reproduction.
Keywords: Climatic changes -- Government policy; Climatic changes -- International cooperation; Climatic changes -- Political aspects